The Impact of Calcined Electrolytic Manganese Residue on the Sulfate Resistance of Cement-Based Materials - Jia Zhenyu (E3S Web of Conferences)
To investigate the sulfate resistance of cementitious materials incorporating electrolytic manganese residue (EMR), EMR samples (10%, 15%, 20%) were prepared by activating EMR at 800°C. The mass and compressive strength of specimens at various carbonation ages were measured, and the pore size distribution at different soaking ages was analyzed using nuclear magnetic resonance (NMR). Results indicate that the incorporation of calcined EMR enhances the sulfate attack resistance of cement mortar, with optimal performance observed at a 15% EMR content. During the initial immersion phase, both the mass and compressive strength of 15% EMR cement mortar and the control group showed positive increases. After 180 days of immersion, the mass of 15% EMR cement mortar continued to increase, and its compressive strength exceeded that of the control group by 18.53 MPa. Additionally, the pore signal of 15% EMR cement mortar was lower compared to all other specimens, indicating denser pores less susceptible to sulfate erosion. Overall, these findings provide theoretical support for the utilization of electrolytic manganese residue in cement- based materials.